Influence, information and team outcomes in large scale software development - DATTA, Subhajit (Institutional Knowledge at Singapore Management University, 2019)
It is widely perceived that the egalitarian ecosystems of large scale open source software development foster effective team outcomes. In this study, we question this conventional wisdom by examining whether and how the centralization of information and influence in a software development team relate to the quality of the team's work products. Analyzing data from more than a hundred real world projects that include development activities over close to a decade, involving 2000+ developers, who collectively resolve more than two hundred thousand defects through discussions covering more than six hundred thousand comments, we arrive at statistically significant evidence indicating that concentration of information and influence in the developer communication networks of the projects are associated with the quality of a team's work products, even after controlling for various factors related to levels of developer engagement. Our results suggest that merely facilitating easy interaction between team members may not be sufficient to enhance team outcomes. The design of efficient collaborative development environments, and devising tools and processes for team assembly and governance can be informed by our results.